Virtual reality in a children’s hospital - Nihei, Kenji; Shirakawa, Kimiko; Isshiki, Nobuo; Hirose, Michitaka; Iwata, Hiroo; Kobayashi, Noboru (The Turkish Journal of Pediatrics, 1999)
We used virtual reality technology to improve the quality of life and amenity of in-patients in a children’s hospital. Children in the hospital could enjoy a zoo, amusement park, and aquarium, in virtual. They played soccer, skiing and horse riding in virtual. They could communicate with persons who were out of the hospital and attend the school which they had gone to before entering hospital. They played music with children who had been admitted to other children’s hospitals. By using this virtual technology, the quality of life of children who sufferd from psychological and physiological stress in the hospital greatly improved. It is not only useful for their QOL but also for the healing of illness. However, these methods are very rare. Our systemic in our children’s hospital is the first to be reported in Japan both software and hardware of virtual reality technology to increase the QOL of sick children need further development.